A comparison of the bipedicled nerve flap with the Littler flap for reconstructing a neurocutaneous defect of digits. Issue 4 (April 2019) - Chen, Chao; Meng, Zhao; Tang, Peifu; Zhao, Gang
Highlights: Bipedicled nerve flap rather than Littler flap may attain better outcomes. Repair of the transected digital nerves can reduce neuroma incidence. Pain is highly related to patient satisfaction. Pain prevention is more important than sensory restoration when reconstructing a digital neurocutaneous defect. Abstract: Background: Complex digital injuries involving soft-tissue loss and digital nerve defect continues to pose a reconstructive challenge. This study reports the repair of such neurocutaneous defect with the bipedicled nerve flap or the Littler flap and compares the results of the two techniques. Methods: A retrospective study was conducted in 59 patients who had a neurocutaneous defect in the single digit treated with the bipedicled nerve flap or the Littler flap from Jul 2008 to May 2016. The patients were divided into two groups based on which flap was chosen. At the final follow-up, the two groups were compared for static two-point discrimination and Semmes-Weinstein monofilament scores on both flap and pulp, and pain, cold intolerance and patient satisfaction of the reconstructed digit. Results: Significant differences were found in static two-point discrimination, pain, cold intolerance, and patient satisfaction (p < 0.05). In comparison with the bipedicled flap group, the Littler flap group presented better discriminatory sensation in the flap and pulp, but exhibited higher incidence of pain and cold intolerance in the reconstructed digit. In the donor digits, the bipedicled flap group achieved lower pain incidence. Finally, the bipedicled flap group attained a larger degree of satisfaction than the Littler flap group. Conclusions: When reconstructing a complex neurocutaneous defect in the digit, choosing the bipedicled nerve flap rather than the Littler flap attains lower incidence of pain and cold intolerance, and higher patient satisfaction. Our results suggest that repair of the transected digital nerves can reduce neuroma incidence.